Numerical simulation of the bulk forming process to manufacture coupling details from tube billet - Ha Linh, Phan Thi; Trung, Nguyen Dac (Vietnam Journal of Science and Technology, 2017)
Currently, most coupling details in the actuators are made by traditional methods such as bulk forming from block billet and then metal cutting. Such manufacturing methods often lead to material wastes due to cutting a large amount of excess processing. To save material and improve production efficiency, tube billet would be selected for bulk forming. However, when tube billet is used for bulk forming, it should be carefully calculated to avoid instability and folding defects in workpiece. This article presents the research on the forming process of the coupling details using numerical simulation and based on the obtained results, the suitable geometric size of tube billet for the forming operation in closed die can be determined.